Indian Urban Households' Access to Basic Amenities: Deprivations, Disparities and Determinants. (August 2015) - Kumar, Arjun
The need for access to basic amenities—drinking water, sanitation, electricity and drainage—to ensure a decent quality of life has been internationally and nationally recognised and acted upon in the form of Millennium Development Goals (MDGs) and various policies and programmes in India. Deprivation and disparities in access to basic amenities in urban India have been highlighted in this article, using data from Census 2001 and 2011 and National Sample Survey's (NSS) Housing Conditions Rounds unit records data 1993 and 2008–09. Determinants of households having access to basic amenities in the house have been estimated using an econometric exercise on household-level information (NSS, 2008–09). Despite improvement over time, many households in urban India still face deprivations of basic amenities and, hence, low standard of living. Households located in slums and small and medium towns/cities and those belonging to Poor, Scheduled Tribe, Scheduled Caste and Wage Labourers (Casual Labourers) groups were highly deprived of access to basic amenities, and disparities among various socioeconomic groups were observed to be increasing. Findings suggest the need for urgent attention for providing basic amenities, focused on slums, small and medium towns/cities and supplemented with inclusive, group-specific measures in order to raise the overall quality of life and well-being.